Hubungan Antara Pola Asuh Orang Tua terhadap Kemampuan Adaptasi Anak Usia Dini di PAUD An-Nisa Kota Gorontalo - Dea Lamaduno; Adita Putri Rauf; Anisa Putri Rahim; Salsiyo Lamatupu; Asma Y. Latif; Sulastya Ningsih (ICHIGO: Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2025)
This research was carried out to portray the parenting practices used by parents and the adaptability of children at PAUD An-Nisa, as well as to analyze the connection between these two aspects. The results reveal that the parenting styles of parents are at a moderate level, indicating that parenting is generally adequate but still needs improvement, particularly in communication, discipline, and emotional support. Meanwhile, children’s adaptability is categorized as good, demonstrated by their ability to interact, manage emotions, and adjust to the learning environment at the PAUD. The analysis further identifies a positive correlation between parenting style and children’s adaptability. This suggests that the better the parenting approach, the stronger the child’s ability to adapt to the school setting. Nevertheless, a child’s adaptability is influenced not only by parenting practices but also by factors such as the learning environment at PAUD, teacher involvement, interactions with peers, and individual child characteristics. In conclusion, the study highlights that parenting style plays a significant role in enhancing children’s adaptability, though successful adjustment also depends on a supportive educational environment and effective collaboration between parents and the school.